2005
DOI: 10.1007/s10704-005-2266-y
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete self-similarity and fatigue-crack growth

Abstract: The Paris power law, which relates fatigue-crack growth rates to the applied stress-intensity range, is an example of a scaling law with the inherent property of incomplete similarity. Previous considerations of dimensions and self-similarity have suggested that the assumed 'materials constants' in this law are also a function of specimen size. In this note, the question of the size-dependence of the Paris law is re-examined, and through comparison to a larger body of fatigue-crack growth data in steels, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 20 publications
0
51
1
1
Order By: Relevance
“…2). The values of the critical scale l sc for various stages of crack propagation are presented in the table.Manifestations of the self similar nature of the fatigue crack growth were studied using methods of the theory of similarity and dimensionality [6,7]. The crack growth rate was defined as a = dl/dN (where l is the crack length and N is the number of cycles) and studied as for correlation with the following parame ters: a 1 = ΔK, stress intensity coefficient; a 2 = E, Young's modulus; a 3 = l sc , correlation scale in the ensemble of defects; a 4 = L pz , the scale related to the process zone.…”
mentioning
confidence: 99%
“…2). The values of the critical scale l sc for various stages of crack propagation are presented in the table.Manifestations of the self similar nature of the fatigue crack growth were studied using methods of the theory of similarity and dimensionality [6,7]. The crack growth rate was defined as a = dl/dN (where l is the crack length and N is the number of cycles) and studied as for correlation with the following parame ters: a 1 = ΔK, stress intensity coefficient; a 2 = E, Young's modulus; a 3 = l sc , correlation scale in the ensemble of defects; a 4 = L pz , the scale related to the process zone.…”
mentioning
confidence: 99%
“…If in addition to the fatigue mode (striations) ductile tearing occurs (e. g. dimples), crack propagation is accelerated and the slope m shall increase [15,16].…”
Section: (2010) 11-12mentioning
confidence: 99%
“…Small width specimens have been used in the literature [19,20], but how these fatigue crack propagation data correlate with those of large width specimens has not been commented. Thus, questions on validity and equivalency of data due to the size effect cannot be excluded when variations in the fracture mode [14][15][16] are likely to occur.…”
Section: (2010) 11-12mentioning
confidence: 99%
“…Botvina, processing the data by Heiser and Mortimer [33] (see [32]), and R.O. Ritchie [34], processing the data by Knott and Ritchie [35] (Figures 7 and 8), showed that the dependence of m upon Z, i.e., upon the specimen size can be substantial. Therefore, using in practical structural design of the results of the standard fatigue experiments performed on small specimens can be dangerous: the real life-time of the structure can be overestimated.…”
Section: Paris Law -An Example Of Incomplete Similaritymentioning
confidence: 99%